Cultural sustainability and Estonian community houses - Kulbok-Lattik, Egge; Roosalu, Triin; Saro, Anneli (Frontiers in Political Science, 2024)
This article explores the role of Estonian community houses in supporting sustainable cultural development and the vitality of communities in a turbulent era of global change. It poses the following questions: (1) How do the representatives of community houses perceive their roles and challenges? (2) How does organizational agency and cultural policy (at national and sub-national level) contribute to cultural sustainability in the context of such disruptions? To answer the first question, in 2022 an online questionnaire survey targeting representatives of Estonian community houses was conducted. The article is based on quantitative and qualitative analysis of 126 responses. The second question provides historical, political, and cultural context to address the first. Estonian community houses, numbering 376 in operation today, are a unique network to study. In the nineteenth century, these cultural hubs became the basis for the system of non-formal life-long education, arts and culture, and later regulated and developed within the subnational politics of culture and education in the Estonian nation-state (1918–40), in the Soviet Union (1940–91), and in today's Estonia (1991–2023) as part of the European Union. The COVID-19 pandemic added a new set of disruptions. In this light, the continuity of the functioning of community houses, alongside their ability to adapt, becomes particularly important for both local communities and sustainable cultural development.